Multimedialití alle Terme di Diocleziano - Carlotta Caruso (mediaGEO soc. coop., 2021)
Between 2010 and 2020 the National Roman Museum - Baths of Diocletian renewed the layout of the Museum of Written Communication of the Romans and the spaces of the monumental complex. In this general revision of its equipment, the use of technologies had a great importance at the service of museum communication to the public. Together with traditional systems (captions and room panels), the technological devices themselves became part of the set-up by integrating and completing the information in order to obtain engaging and effective methodologies.